Complaint Strategies Used By Indonesian EFL Learners In Muhammadiyah University Of Surakarta Viewed From Social Distance, Status, And Gender - Astika, Dheftya Cahya, Agus Wijayanto, Ph.D, Dra. Malikatul Laila, M.Hum (2013)
This research describes the differentiated of complaint strategies use in complaint relation ofdistance, status (relative power), and gender by Indonesian EFL learners in Muhammadiyah University of Surakarta. This constituted descriptive research in which the research participants of this research were fifty the first semester of Indonesian EFL learners at English department in Muhammadiyah University of Surakarta. The data were on the spoken utterance form, of complaint strategies obtained through oral DCT (Discourse Completion Task) scenarios. The subjects of the research were taken using proportional random sampling technique consisting twenty five male and twenty five female EFL partisipants. The writer analyzed the data of complaint strategies basd on Trosborg (1995). The writer also conected the research with sociopragmatics theory about the relation of complaint strategies with distance, status (relative power), and gender. The result findings showed that there are any differences in the use of complaint strategies based on different status (relative power), distance, and gender.